Tracing Troops: An Upper German Belt-Fitting from Roman Scotland. (2nd May 2016) - Hunter, Fraser
ABSTRACT: A silver belt-fitting from Cramond in the shape of a ring-pommel sword is linked to a class of beneficiarius equipment typical of Germania Superior. It is argued that this represents troop movements connected with the Severan campaigns.